To find the expression equivalent to \( 9x^2 - 25 \) using the Distributive Property, we recognize that this expression resembles the difference of squares, which is in the form \( a^2 - b^2 \) and can be factored as \( (a + b)(a - b) \).
Here, we can identify:
- \( a^2 = 9x^2 \) implies \( a = 3x \)
- \( b^2 = 25 \) implies \( b = 5 \)
Therefore, we can rewrite the expression \( 9x^2 - 25 \) as:
\[ 9x^2 - 25 = (3x)^2 - 5^2 \]
Using the difference of squares formula, we can factor it:
\[ (3x + 5)(3x - 5) \]
Thus, the expression that is equivalent to \( 9x^2 - 25 \) is:
\[ (3x + 5)(3x - 5) \]
The correct answer is:
(3x + 5)(3x - 5)